PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS DITINJAU DARI GAYA KOGNITIF - Rachmat Rachmat; Hepsi Nindiasari; Maman Fathurrohman (Universitas Islam Nusantara, 2020)
The purpose of this study was to analyse the influence of the Teams Games Tournament (TGT) learning model against thestudent’s mathematical reflective thinking skills based on cognitive styles. The results showed that: (1) student’s mathematicalreflective thinking skills learning with the Teams Games Tournament learning model are higher than those using scientificlearning models; (2) Mathematical reflective thinking skills between students who have field independent cognitive style andfollow learning with the Teams Games Tournament learning model is lower than those students who have field dependentcognitive style (3) Mathematical reflective thinking skills between students who have a field independent cognitive style andfollow learning with the Teams Games Tournament learning model higher than the students who follow the learning modelScientific learning; (4) Mathematical reflective thinking skills between students who have a field dependent cognitive styleand follow learning with the Teams Games Tournament learning model higher than the students who follow learning withthe learning model Scientific (5) There is no influence of interaction between learning models with cognitive style to themathematical reflective thinking skills of students